Analisis Pengaruh Remunerasi, Manajemen Risiko dan Tata Kelola Perusahaan terhadap Kinerja Keuangan pada BUMN di Indonesia Tahun 2019-2023 - Raihan Razif Afero (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Healthy financial performance is a target that a company wants to achieve which can be influenced by many factors both internally and externally. In this study, remuneration, risk management and corporate governance are the variables chosen to find their influence on financial performance. State-owned enterprises or BUMN are the research samples with a total of 20 BUMN from 2019 - 2023. Qualitative descriptive analysis methods are used with secondary data as a supporting tool for the research. Secondary data comes from journals, articles or annual reports of companies in the form of non-numerical data such as standards, policies or rules used in BUMN operations. The results of the study show that remuneration, risk management and corporate governance do not affect financial performance for various reasons. Remuneration has no effect because the number of workers from each BUMN is different and has a different remuneration policy. While risk management has no effect because liquidity risk cannot be the only risk that can be used, meaning that there needs to be intervention from other risks. Corporate governance has no effect because of the difference in the number of directors and the change of directors which results in changes in policy or culture.